Targeted Next‐Generation Sequencing for Comprehensive Genetic Profiling of Pharmacogenes. Issue 3 (24th November 2016) - Han, SM; Park, J; Lee, JH; Lee, SS; Kim, H; Han, H; Kim, Y; Yi, S; Cho, J‐Y; Jang, I‐J; Lee, MG
Abstract : Phenotypic differences in drug responses have been associated with known pharmacogenomic loci, but many remain to be characterized. Therefore, we developed next‐generation sequencing (NGS) panels to enable broad and unbiased inspection of genes that are involved in pharmacokinetics (PKs) and pharmacodynamics (PDs). These panels feature repetitively optimized probes to capture up to 114 PK/PD‐related genes with high coverage (99.6%) and accuracy (99.9%). Sequencing of a Korean cohort ( n = 376) with the panels enabled profiling of actionable variants as well as rare variants of unknown functional consequences. Notably, variants that occurred at low frequency were enriched with likely protein‐damaging variants and previously unreported variants. Furthermore, in vitro evaluation of four pharmacogenes, including cytochrome P450 2C19 ( CYP2C19 ), confirmed that many of these rare variants have considerable functional impact. The present study suggests that targeted NGS panels are readily applicable platforms to facilitate comprehensive profiling of pharmacogenes, including common but also rare variants that warrant screening for personalized medicine.